2017
DOI: 10.1002/prp2.360
|View full text |Cite
|
Sign up to set email alerts
|

Methionine and vitamin B‐complex ameliorate antitubercular drugs‐induced toxicity in exposed patients

Abstract: Tuberculosis therapy utilizes drugs that while effective cause treatment‐related toxicity. Modulation of antitubercular drugs‐induced toxicity by methionine and vitamin B‐complex in patients was evaluated. 285 treatment‐naïve tuberculosis patients at the Chest Clinics of Infectious Diseases Hospital, Yaba and General Hospital, Lagos in Lagos, Nigeria was prospectively recruited and allotted into test (antitubercular medicines, methionine and vitamin B‐complex) and control groups (antitubercular medicines). Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Although the mechanism of hepatotoxicity of the drug seems unclear, oxidative stress caused by free radical metabolites of drugs has been strongly linked to this adverse drug reaction and a number of studies have demonstrated the presence of oxidative stress amongst patients with drug induced hepatotoxicity 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of hepatotoxicity of the drug seems unclear, oxidative stress caused by free radical metabolites of drugs has been strongly linked to this adverse drug reaction and a number of studies have demonstrated the presence of oxidative stress amongst patients with drug induced hepatotoxicity 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Administering vitamins B1, B6, and B12 can increase the number of T lymphocytes and the activity of Natural Killer cells (NK cells), both of which can trigger the release of interferon-gamma (INF-γ). Giving vitamins can reduce the risk of recurrence of tuberculosis by 45 % and reduce the incidence of extrapulmonary tuberculosis (14).…”
Section: Introductionmentioning
confidence: 99%
“…Anti-TBC therapies are known for their hematological adverse events, in particular isoniazid-induced anemia, through the superoxide generation and the blockade of heme synthesis [15,16]. Also, ruxolitinib may cause or contribute to anemia in MF.…”
Section: Introductionmentioning
confidence: 99%